P38 is involved in immune response by regulating inflammatory cytokine expressions in the Pacific oyster Crassostrea gigas. (February 2019) - Sun, Jiejie; Wang, Lingling; Wu, Zhaojun; Han, Shuo; Wang, Liyan; Li, Meijia; Liu, Zhaoqun; Song, Linsheng
Abstract: P38 mitogen-activated protein kinases are serine/threonine protein kinases reportedly involved in the innate immunity of vertebrates and invertebrates. In the present study, a P38 homolog ( Cg P38) was characterized from the Pacific oyster Crassostrea gigas . The full-length cDNA of Cg P38 was of 1515 bp containing a 1101 bp open reading frame. A serine/threonine protein kinase (S_TKc) domain with a conserved Thr–Gly–Tyr motif and an ATRW substrate-binding site was found in the deduced amino acid sequence of Cg P38. Cg P38 shared a close evolutionary relationship with Ch P38 from the Hong Kong oyster Crassostrea hongkongensis . The transcript levels of Cg P38 in hemocytes increased significantly from 12 h to 48 h after lipopolysaccharide (LPS) stimulation and from 12 h to 24 h after Vibrio splendidus stimulation. The phosphorylation level of Cg P38 in oyster hemocytes increased significantly at 2 h after LPS stimulation. Cg P38 positively regulated the expression of interleukins, such as Cg IL17-1, Cg IL17-2, Cg IL17-3, Cg IL17-4 and Cg IL17-6, and tumor necrosis factor Cg TNF after LPS or V. splendidus stimulation. These results suggested that Cg P38 participated in oyster immune response by regulating the expressions of inflammatory cytokines. Highlights: A P38 homolog was identified from oyster Crassostrea gigas. The expression level of Cg P38 increased significantly after LPS and Vibrio splendidus stimulations. LPS induced Cg P38 phosphorylation in oyster hemocytes. Cg P38 regulated the production of Cg IL17s and Cg TNF in oysters after LPS and Vibrio splendidus stimulations.